UJI DAYA TERIMA DAN ANALISI KANDUNGAN ZAT GIZI FORMULA BUBUR ISNTAN TEPUNG TALAS (Colocasia Esculenta) DAN TEPUNG IKAN PATIN (Pangasius Hypopthalmus) SEBAGAI ALTERNATIF UPAYA PENCEGAHAN STUNTING PADA ANAK BALITA - Dea Rif'atushalihah; Jonni Syah R. Purba; Iman Jaladri (Jurusan Gizi Poltekkes Pontianak, 2026)
Stunting is a form of growth-faltering failure due to the accumulation of nutritional deficiencies that last a long time, from pregnancy to 24 months of age. Insufficient protein and calcium consumption are factors that cause stunting. Some efforts must be made to improve healthy behavior, with a special focus on consumption behavior. Therefore, researchers want to investigate the production of MP-ASI, namely instant porridge made from pangas catfish flour and taro flour, which can increase protein intake. This study was to determine the acceptability and nutritional content of instant porridge made from taro flour and pangas catfish flour as an alternative effort to prevent stunting in toddlers. This study used an experimental design consisting of three treatments, namely taro flour and pangas catfish flour in Formula 1 (85:15), Formula 2 (70:30), and Formula 3 (55:45). The test was carried out in two stages, namely the organoleptic test to see the level of panellists' preference for instant porridge with a sample of 25 panellists and a test of nutritional content, namely protein, carbohydrates, fat, and calcium. The study analyzed three instant porridge formulas: F1 (85% taro flour: 15% pangas catfish flour), F2 (70% taro flour: 30% pangas catfish flour), and F3 (55% taro flour: 45% pangas catfish flour). The results showed that F3 (55% taro flour: 45% pangas catfish flour) was the best formula, with protein (23.97 g), carbohydrates (44.54 g), fat (15.74 g), and calcium (2.12 g). There are differences in aroma, taste, texture, and color in the acceptability of instant porridge with taro flour and pangas catfish flour as the basic ingredients.